The influence of external economic policy fluctuation on enterprise productivity: Based on Chinese listed enterprises - Jia, Songbo; Gao, Xin; Zhu, Xiaowen; Xu, Jianxiang; Liu, Yuanyuan (Technological and Economic Development of Economy, 2025)
Drawing upon a comprehensive dataset encompassing Chinese publicly traded enterprises across the two-decade span from 2000 to 2020, this article analyzes the effects of external economic policy variations on the productivity of Chinese enterprises. The consequences show that when facing the aggravation of external variations in economic policy, enterprises prefer to enhance total factor productivity and labor productivity to reduce the risk caused by the expansion of external uncertainty. Moreover, the greater the degree of internationalization of an enterprise, the higher its vulnerability to variations in external economic policies. The mechanism test shows that for enterprises that only participate in domestic circulation, external economic policy fluctuations improve productivity by affecting the operating environment; however, when enterprises join in the dual circulation, the fluctuations will promote productivity by affecting the scale of enterprises’ overseas business instead. First published online 6 November 2024